Percursos entre ruas, escritas e modos de subjetivação - Krepschi, Amaranta Gasperotto (2013)
This research is enlivened by the possibility of creating through writing, by the act of noticing and noting the affections of the living body in its relationship with writing. It speaks of experimentations with and departing from writing. It is also an invitation for the reader to follow this route which begins with the streets of Lisbon in 2008 and 2009 (while I was in artistic residency at c.e.m.); continues by crossing the Atlantic Ocean, and flows into the city of São Paulo through the winding streets of Vila Anglo-Brasileira. This research accompanies the mode "how" hegemonic politics of subjectivization affects the dancing, writing, loving and paralyzing body that transits throughout different cities. It follows the moments when and the agencies with which it was possible to create different modes of being with (the city, the street, fear, writing, flows, desire). For this research, writing plays a singular and important role, as it has been the most outstanding company for such passages. Sometimes becoming the passage itself